Saat-Saat Penting: Pengalaman Berharga dalam Proker KKN Memandikan dan Mengafani Jenazah - Chaidar, Muhammad Raihan (TAFANI: Jurnal Pengabdian Masyarakat, 2024)
Death is an inevitable event in the lives of all creatures, including humans. Regardless of when and how death occurs, the responsibility for handling a deceased individual becomes crucial for those who are still alive. Religion, especially Islam, provides comprehensive guidelines on how to deal with the deceased. However, in everyday life, many Muslims are not well-versed in the proper procedures for conducting funerals in accordance with their religious teachings.This article outlines the importance of understanding the procedures for managing funerals, considering aspects such as religious and cultural significance, paying final respects, complying with legal and administrative requirements, ensuring hygiene and health considerations, providing psychological support, preparing in advance, and maintaining efficiency and organization. Funeral management can be categorized as a collective duty known as "Fardhu Kifayah," where the responsibility lies collectively with the community, and if performed by some individuals, it absolves others from the obligation. Therefore, this article aims to provide a systematic and comprehensive practical guide on funeral management, with a focus on the understanding of the residents of Tanjung Batu village regarding the procedures for washing and shrouding the deceased. Despite the village having designated personnel for funeral management, the role of the family remains paramount. The article also notes that while some village residents have a basic understanding of the correct procedures, many forget the sequence, highlighting the need for a proposed program to provide the necessary training in funeral management.